PENANGANAN KONSERVASI TANAH DAN AIR BERBASIS UNIT EKOLOGIS DI SUB DAS NGRANCAH, KULON PROGO - , Ambar Kusumandari, Ir.,MES. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Land exploitation without considering its carrying capacity will result the land degradation includes the increasing rates of erosion, sedimentation and critical land. Thus, the degraded land should be managed properly and sustainability. So, the objective of this research is to study the land characteristics to determine the ecological units, to estimate the erosion rates, and to propose the appropriate soil and water conservation techniques. The USLE Model was used for predicting the erosion rates, A = RKLSCP. The land was classified using cluster analysis to get the dendrogram. The ecological unit was clustered based on: a) vegetation, b) soil characteristics, c) erosion rates, d) all of land parameters, and e) main land parameters. To determine the main parameter, discriminant analysis was carried out. The research resulted that: a. Based on the land characteristics, the Ngrancah sub watershed can be divided into 77 ecological units or classified as less in variation. b. Cluster analysis based on the vegetation, soil characteristics, erosion, and all land parameters respectively resulted in percent canopy, chemical soil fertility, soil erodibility, and soil fertility as the main parameters that results respectively 93.55